Demographic and Clinical Features of Small-for-Gestational-Age Infants Born to Mothers With Gestational Diabetes Mellitus - Chen, Juncao; Xiao, Huimin; Yang, Yong; Tang, Yaping; Yang, Xiaoqi; Zhang, Zhe; Lu, Weineng; Yao, Jie; Huang, Longguang; Liu, Xiaoping; Zhou, Wei (Frontiers in Pediatrics, 2021)
We studied the demographic and clinical characteristic, risk factors, outcomes of full-term small-for-gestational-age (SGA) infants born to mothers with gestational diabetes mellitus (GDM) in China. A retrospective case-control study that included 1981 SGA infants was conducted; the demographic and clinical data between SGA infants born to mothers with and without GDM were compared. Of 383 SGA infants born to mothers with GDM, 221 (57.7%) were female, and the incidence of these infants was 1 in 155 live births. The risk of SGA siblings (RR, 1.88; 95% CI,[1.23-2.86]), low 1- and 5-min Apgar scores (RR,2.04 and 4.21; 95%CI [1.05-4.00] and [1.05-16.89], respectively ), early thrombocytopenia (RR, 3.39; 95%CI, [1.33-8.64]), hypoglycemia(RR, 2.49; 95%CI, [1.55-3.98]), and hypoxic-ischemic encephalopathy (RR,5.61; 95%CI, [1.25-25.18]) were increased in SGA infants born to mothers with GDM compared to SGA infants born to mothers without GDM. SGA girls born to mothers with GDM had a significantly higher ratio of catch-up growth (CUG) (RR, 1.73; 95%CI, [1.18-2.54]) in the first year of life. These results show that genetic factors may be one of the etiologies of SGA infants born to mothers with GDM; and these infants have more adverse perinatal outcomes compared to SGA born to mothers without GDM. SGA girls born to mothers with GDM had accelerated CUG in the first year of life.